Linguistic diversity and the translation process as a guarantee of human rights - Calixto, Patrícia Mendes; Pottmeier, Sandra (Revista Hipótese, 2025)
This article sought to analyze the importance of linguistic diversity and the translation process as a guarantee of human rights. It is a study with a qualitative approach based on documentary research. The results indicated that studies in the field of Language Sciences and Education are still in their infancy regarding the discussion on the relationship between linguistic diversity and human rights. It is considered that it is necessary to value linguistic diversity by understanding it as a basic human right, especially when considering the context from which the individual who is away from their home originates, for whatever reason. It also emphasizes the importance of welcoming this person, particularly in public spaces, where essential rights such as access to security, health, and education must be guaranteed for their individual and collective well-being.
Keywords: Linguistic Diversity; Translation; Human rights; Identities